Prophylaxis and therapy of HBV infection in 20 patients treated with disease modifying antirheumatic drugs or with biological agents for rheumatic diseases - C. Bazzani; M. Frassi; P. Airò; S. Zingarelli; M. Scarsi; M. Puoti (PAGEPress Publications, 2011)
Hepatitis B virus (HBV) is a DNA virus transmitted predominantly by sexual contact or percutaneous exposure. HBV infection is by far the most common chronic viral infection affecting the liver in the world, and a leading cause of cirrhosis and hepatocellular carcinoma. Reactivation of HBV replication in patients undergoing immunosuppressive therapy is a well recognised and frequently reported complication of considerable clinical importance. The consequences of hepatic injury in these patients may range from asymptomatic liver function disturbances to massive hepatic necrosis, liver failure, and death (1-2).